Water‐cooled magnetic coupling drive attenuator design for wiggler light source in the TPS 31A beamline. (1st April 2022) - Hsu, Ming-Ying; Lee, Chien-Yu; Fung, Hok-Sum; Chen, Bo-Yi; Yin, Gung-Chian
Abstract : A water‐cooled magnetic coupling attenuator design is presented. Abstract : An attenuator is generally used to decrease the power of an X‐ray beam and prevent damage to detector sensors and other optical components. Therefore, attenuators are designed using foil or gas to absorb light source power. In this project, a large aperture and a water‐cooling attenuator system are construed for the TPS 31A Projection X‐ray Microscope and Transmission X‐ray Microscope beamline. The source size of the wiggler is 300 µm × 7 µm on TPS 31A. The X‐ray beam size at the sample position is 50 mm × 20 mm, located 49.5 m from the source. The light emission power is 1000 W in white‐beam operation mode. The attenuator is needed to absorb energy for the light source and it has 12 foil carriers. The absorption foil size is 56 mm × 46 mm for the beam size across different beamline operation modes, and the cooling capacity is greater than 1000 W. This study applies a magnetic coupling‐type attenuator system with foil carrier cooling carried out by the side chamber walls without the feedthrough having water enter the chamber to solve the thermal dissipation issue.